2020
DOI: 10.1016/j.jsxm.2020.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Partner Sexual Concerns During the First Year After an Implantable Cardioverter Defibrillator: A Secondary Analysis of the P+P Randomized Clinical Trial

Abstract: Background Sexual concerns and changes in sexual activity are common among patients and their intimate partners after an implantable cardioverter defibrillator (ICD). Aims Our aims were to (i) describe patient and partner sexual activity and related concerns from the time of an initial ICD implant through 12-month follow-up and (ii) identify factors predictive of return to sexual activity and fears associated with sexual acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Review of item‐level concerns also noted that 41% of patients reported being able to return to sexual activity, which is consistent with other studies noting 47% of patients with an ICD being sexually active 12 months after ICD implantation. 34 The VA clinic can be vital at counseling patients, appropriately allowing them to return to sexual activity once their concerns are addressed. 35 , 36 By using item‐level analysis of PROMs, the clinician is able to address specific patient concerns to improve their overall well‐being, which may not be readily observed when reviewing overall PROM scores.…”
Section: Discussionmentioning
confidence: 99%
“…Review of item‐level concerns also noted that 41% of patients reported being able to return to sexual activity, which is consistent with other studies noting 47% of patients with an ICD being sexually active 12 months after ICD implantation. 34 The VA clinic can be vital at counseling patients, appropriately allowing them to return to sexual activity once their concerns are addressed. 35 , 36 By using item‐level analysis of PROMs, the clinician is able to address specific patient concerns to improve their overall well‐being, which may not be readily observed when reviewing overall PROM scores.…”
Section: Discussionmentioning
confidence: 99%